2010
DOI: 10.1182/blood-2009-08-237768
|View full text |Cite
|
Sign up to set email alerts
|

Donor and recipient chemokine receptor CCR5 genotype is associated with survival after bone marrow transplantation

Abstract: Despite continual improvement, morbidity and mortality after hematopoietic stem cell transplantation (HSCT) remain high. The importance of chemokines in HSCT lies in their regulation of immune responses that determine transplantation outcomes. We investigated the role of recipient and donor chemokine system gene polymorphisms by using a candidate gene approach on the incidence of graft-versus-host disease and posttransplantation outcomes in 1370 extensively human leukocyte antigen-matched, unrelated donor-reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Although studies in mice that are genetically deficient for Ccr5 have shown conflicting results, 15,17-19 genetic evidence in humans shows that certain CCR5 polymorphisms are protective against GVHD 20,21 and correlate with survival in patients undergoing allogeneic HSCT. 22 …”
mentioning
confidence: 99%
“…In bone marrow transplants, CCR5 presence on CD4 + T-regulatory cells is important in prolonging graft survival (Wysocki et al, 2005). This was corroborated by a study, which showed that CCR5 genotypes with higher levels of expression have a significant survival outcome (McDermott et al, 2010). However, contrary to these findings, Bogunia-Kubik et al demonstrated that Δ32 individuals have a reduced likelihood of developing graft vs .…”
Section: Role Of Ccr5 Deficiency In Diseasementioning
confidence: 63%